Análisis económico de la industria de muebles de madera en Colombia con una perspectiva desde el sector forestal (1991 – 2010) (2014)
Colombia has a potential timber production, as it has fertile soils and a variety of timber “The country has a total area close to 114 million hectares; of which more than 60 million have coverage of natural forest, equivalent to 55% of Colombia’s national territory and only 405,000 hectares are planted forests which about 377,000 have commercial purposes” (Minagricultura, 2011).